Amelioration and arable land-use possibilities of Solonetz soils in the Trans-Tisza region of Hungary - Blaskó, Lajos (Acta Agraria Debreceniensis, 2018)
Salt affected soils cover about 1 million hectares in Hungary. This paper is based on the research results obtained at the Karcag-puszta long-term experimental site, where, depending on the catena, crusty (A horizon=0–7 cm), medium (A hor.=8– 20 cm) and deep (A hor.>20 cm) subtypes of the Meadow Solonetz soil could be found. The chemical reclamation was made specifically for the given site. Lime was applied on the soils with neutral or slightly acidic top layer, while on the soils with alkaline top layer, gypsum was applied. As regards internal drainage, a tube system with an average depth of 1 m and 5, 10 and 15 m drain spacing was constructed. Decreasing salt and sodium content could be measured both in drained and non-drained soils. The advantage of drainage was that the leachingout extended to the whole layer above the drain pipes, while without drainage, the Na ions exchanged from the upper layers still accumulated at a depth of 60– 100 cm. In the first two decades, the groundwater level was deeper and leaching was the dominant process. Since 2004, due to the frequently high groundwater level, the leaching and deepening of the fertile top layer has been slower.